Faculty Promotions: An Analysis Of Central Administrative Control - Luthans, Fred (Academy of Management Journal, 1967)
Very little significant research has been conducted on the university as an organized activity. This study helps to fill some of this void. The concept of central administrative control is used as a framework to empirically analyze faculty promotion policies and practices.